Naturalized exotic plants with invasive potential in peri-urban areas of the high Ecuadorian Amazon - Carvajal, Edison (2020)
Invasive alien species are the second cause ofbiodiversity loss on the planet. Additionally,globalization and climate change are favoring its entryinto areas that have not been humanized in the past, suchas the Ecuadorian Amazon. The cantonal capital of Puyohas numerous exotic plants already reported in other partsof the world as invaders, which here have been observedand identified to provide listings and information aboutwhich naturalized species in the future can becomeinvasive under the scenarios of climate change. , andalso propose among them four exotic species with thegreatest potential to behave as invasive with the currentclimate. The fieldwork was carried out in the periurbanenvironment of Puyo, identifying the specieswith herbarium samples, also through bibliographic andonline consultations, reporting numerous naturalizedexotic species that were organized hierarchically andselected for their attributes to be potential invaders orcurrent, identifying 15 naturalized exotic species withthe potential to be invasive under the climate changescenarios highlighting 4 plant species that are alreadyor can become in the future a serious problem forbiodiversity and the Ecuadorian Amazonian economy.With this work it is expected that the environmentalauthorities and the inhabitants become aware of theirpresence and apply measures for their early eradication.